CoFe2O4 decorated g-C3N4 nanosheets: New insights into superoxide anion mediated photomineralization of methylene blue. Issue 6 (December 2020) - Ehsan, Muhammad Fahad; Fazal, Anam; Hamid, Saher; Arfan, Muhammad; Khan, Ibrahim; Usman, Muhammad; Shafiee, Ali; Ashiq, Muhammad Naeem
Graphical abstract: CoFe2 O4 decorated g- C3 N4 nanosheets result in enhanced photocatalytic MB mineralization under the visible-light. These results are not only attributed to efficient charge separation and rapid transport in g- C3 N4, but also to the improved photostability and higher conductivity of CoFe2 O4 . Highlights: CoFe2 O4 decorated g -C3 N4 nanocomposite degrades > 93 % of Methylene Blue (MB) dye with ∼ 90 % mineralization under visible-light irradiation. ESR spectroscopy reveals the formation of O2 – as primary ROS which has never been reported employing CoFe2 O4 decorated g -C3 N4 photocatalysts. Alignment of energy levels vs SHE also supports the formation of O2 –. Abstract: Graphitic carbon nitride ( g- C3 N4 ) based photocatalysts have recently gained much attention for environmental remediation. However, the correlation between constituent counterparts in g- C3 N4 based nanocomposites as well as mechanistic understanding related to the reactive oxygen species (ROS) have not been discussed much. Herein, ascribing to the significant thermodynamic potential of surface charge transfer between their conduction bands, we present spinel cobalt ferrite (CoFe2 O4 ) decorated g- C3 N4 nanosheets for photocatalytic mineralization of methylene blue (MB). The ROS are investigated using electron spin resonance (ESR) spectroscopy and the results confirm the formation of superoxide anion radical ( O 2 - ) as primary oxidant. Furthermore, UV–vis-NIR diffuse reflectance spectroscopy (DRS) and X-ray photoelectron spectroscopy (XPS) analysis are utilized to plot alignment of energy levels against standard hydrogen electrode (SHE). The band diagram does not only support the O 2 - formation but also provides interesting insights to explain the degradation dynamics based on the respective band positions in the nanocomposite.